KARAKTERISTIK PEMBELAJARAN PAI DALAM PENDIDIKAN FORMAL - Hafsah (al-Afkar, Journal For Islamic Studies, 2021)
In the Ministry of National Education's Curriculum Center, the purpose of Islamic education is to foster and increase the faith of students through the provision and cultivation of knowledge, appreciation, this research uses a literature study approach. The results of the research show that we all certainly know Islam, but the problem is, what kind of Islam we know it, is actually still an issue that needs to be discussed further. For example, knowing Islam in the portrait presented by Iqbal with its philosophical and mystical nuances. Likewise, Islam is displayed by thoughts from Iran such as Ali Shariaati, Sayyed Hussein Nasr, Murthadha Motahhari, these Islamic thinkers from Iran seem to have mastered the thoughts of Modern Philosophy and social sciences from the west.